Review of Republican Women: Feminism and Conservatism from Suffrage Through the Rise of the New Right. Catherine E. Rymph. Reviewed by Leon Ginsberg - Ginsberg, Leon (2007)
Book review of Catherine E. Rymph, Republican Women: Feminism and Conservatism from Suffrage through the Rise of the New Right. Chapel Hill, NC: University of North Carolina Press, 2006. $24.05 papercover